PENGARUH ONLINE PROMOTION TERHADAP REPURCHASE INTENTION DENGAN CONSUMER PERCEPTION SEBAGAI MEDIASI PADA MAHASISWA FEB UNISMA PENGGUNA TRAVELOKA - Andik Kurniawan; N Rachma; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT            This study aims to find out and analyze the online promotion of repurchase intention with consumer perception as a mediation for FEB Student Traveloka users in Malang Islamic University. The sample in this study were FEB students at the Islamic University of Malang in the 2015-2016 academic year who had used Traveloka with 85 people who had used Traveloka. In this study the technique used was purposive sampling technique or by using criteria. The data source used in this study is primary research with data collection conducted by distributing questionnaires. The data analysis method used in this study used validity, reliability tests, normality tests, path analysis, t test and sobel test.            The results of this study indicate that : 1) online promotion has a direct influence on consumer perception 2) online promotion has a direct influence on repurchase intention 3) consumer perception has a direct influence on repurchase intention and 4) consumer perception is able to be a good mediation between online promotion and repurchase intention.Keywords: Online Promotion, Repurchase Intention and Consumer Perception